Sports Activities High Performance Athletes Muslim Women in Indonesia and Malaysia. (March 2017) - Fitri, M; Sultoni, K; Salamuddin, N; Taib Harun, Mohd
Abstract: Participation in sports activities was also influenced by sociological factors. This indirectly allows individuals more adaptable in high performance sports compared with individuals who did not engage in sports activities. This study aims to identify high performance sports athletes Muslim women in Indonesia and Malaysia in the sport. The quantitative approach was carried out by the study population consisted of Muslim women athletes Malaysia and Indonesia, which joined The 3rd Islamic Solidarity Games. The study sample consisted of 58 Malaysia and 57 Indonesia. Descriptive analysis also shows that sports activities like Muslim women athletes in the ranking of badminton (Malaysia 46.5% and Indonesia 38.6%), swimming (Malaysia 33.3% and Indonesia 57.9%), sports (Malaysia 27.5% and Indonesia at 22.8%), and balls volleyball (Malaysia and Indonesia 17.2%, 29.8%). The results of this study can serve as a guide for the government to make sports facilities more attractive community of Muslim women.